Preparación del presupuesto - Liliedal, Augusto M. (1961)
The author make a general study of the budget and analyses which power should be in charge of its preparation considering the consequences and difficulties which arise in each particular case. He also analyses all proceedings connected with the study, approval or rejection of the budget once it has been presented to Congress. Finally he comments on the consequences of the rejection, delay or veto in budgetary matters as well as on the circumstantial solution which governments should adopt.